2017
DOI: 10.7554/elife.29736
|View full text |Cite
|
Sign up to set email alerts
|

CDK9-dependent RNA polymerase II pausing controls transcription initiation

Abstract: Gene transcription can be activated by decreasing the duration of RNA polymerase II pausing in the promoter-proximal region, but how this is achieved remains unclear. Here we use a ‘multi-omics’ approach to demonstrate that the duration of polymerase pausing generally limits the productive frequency of transcription initiation in human cells (‘pause-initiation limit’). We further engineer a human cell line to allow for specific and rapid inhibition of the P-TEFb kinase CDK9, which is implicated in polymerase p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

27
230
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 198 publications
(257 citation statements)
references
References 55 publications
27
230
0
Order By: Relevance
“…This in turn may be the result of a bottleneck delimited by the +1 nucleosome between ~+50-150bps relative to the TSS. This would be consistent with previous experiments and computational models of Pol II ChIP-seq data which propose that initiation and promoter proximal pausing are intrinsically linked and pausing may only become rate limiting after initiation is saturated (Ehrensberger, Kelly, and Svejstrup 2013;Gressel et al 2017;Gressel, Schwalb, and Cramer 2019).…”
Section: Transcriptional Pausing At the +1 Nucleosomesupporting
confidence: 92%
See 1 more Smart Citation
“…This in turn may be the result of a bottleneck delimited by the +1 nucleosome between ~+50-150bps relative to the TSS. This would be consistent with previous experiments and computational models of Pol II ChIP-seq data which propose that initiation and promoter proximal pausing are intrinsically linked and pausing may only become rate limiting after initiation is saturated (Ehrensberger, Kelly, and Svejstrup 2013;Gressel et al 2017;Gressel, Schwalb, and Cramer 2019).…”
Section: Transcriptional Pausing At the +1 Nucleosomesupporting
confidence: 92%
“…It has been proposed that the density of Pol II found at the promoter proximal region represents paused Pol II and the ratio of this to the density of Pol II throughout the remainder of the body of the gene (the pausing index) has been used as a measure of transcriptional pausing (Muse et al 2007;Rahl et al 2010;Zeitlinger et al 2007). Inhibition of CDK9 causes the pausing index to increase, and this has been interpreted as evidence for regulation of transcriptional pausing (Gressel et al 2017;Jonkers, Kwak, and Lis 2014;Rahl et al 2010). Consequently, changes in the pausing index have been used to suggest that pausing is a key regulatory step in the transcription cycle (Adelman and Lis 2012;Chen, Smith, and Shilatifard 2018;Jonkers and Lis 2015) and that this is regulated by enhancers (Chen et al 2017;Gao et al 2018;Ghavi-Helm et al 2014;Liu et al 2013;Schaukowitch et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Empirical support for this model has recently been obtained from a study in Drosophila cells using ChIP‐nexus, which revealed that the half‐life of paused Pol II correlates inversely with the presence of initiating Pol II, and moreover, that Flavopiridol‐mediated inhibition of Pol II pause release leads to a reduction in the fraction of initiating Pol II (Shao & Zeitlinger, ). Another recent study used analog‐sensitive Cdk9 inhibition and a novel means of calculating initiation frequency and pause duration to reach similar conclusions regarding the control of initiation by pausing (Gressel et al , ). Our findings serve as a corollary to these data by showing that decreased pausing leads to increased initiation.…”
Section: Discussionmentioning
confidence: 92%
“…Since P-TEFb-mediated phosphorylation of NELF and the C-terminal domain (CTD) of Pol II are essential for gene expression in mammals (reviewed in 76 ), it is tempting to speculate that increased P-TEFb concentration at the heat-induced genes could overcome the global transcriptional repression. The entry of new Pol II molecules to the TSS is limited by the rate of release of Pol II into productive elongation 77 , as might be expected from the position of the pause site and the size of the Pol II complex, which causes steric hindrance for new initiation 78 . Coupling P-TEFb-mediated pause-release to the entry of new Pol II 78 molecules might be an important mechanism that drives high transcriptional activity, such as that triggered by heat shock.…”
Section: Reprogramming Of Gene Expressionmentioning
confidence: 99%
“…The entry of new Pol II molecules to the TSS is limited by the rate of release of Pol II into productive elongation 77 , as might be expected from the position of the pause site and the size of the Pol II complex, which causes steric hindrance for new initiation 78 . Coupling P-TEFb-mediated pause-release to the entry of new Pol II 78 molecules might be an important mechanism that drives high transcriptional activity, such as that triggered by heat shock.…”
Section: Reprogramming Of Gene Expressionmentioning
confidence: 99%